Bringing social identities back in: the social anchors of left-right orientation in western Europe - Freire, A. (International Political Science Review, 2006)
This article seeks to show that the relative weight of social factors in explaining individual left-right self-placement, vis-a-vis values and partisan loyalties, is very important, contrary to the poor results shown by prior studies. The bias in previous literature was due to the fact that the models used for social factors were underspecified: they included only structural and organizational dimensions and ignored social identity. However, when the model was correctly specified by adding indicators of social identity, it was possible to reach an opposite conclusion. The cases studied were 12 western European countries (Portugal, Spain, France, Great Britain, Germany, Austria, Italy, the Netherlands, Denmark, Belgium, Sweden, and Ireland) in 1990 and 1999.